Influence of foam rolling on recovery from exercise-induced muscle damage - D'Amico, A. P.; Gillis, J. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to examine the impact of foam rolling (FR) on recovery from exercise-induced muscle damage (EIMD). Thirty-seven male individuals performed 40 × 15-m sprints, inducing muscle damage. Immediately after sprinting and in the 4 days following, perceived muscle soreness, hip abduction range of motion (ROM), hamstring muscle length, vertical jump (VJ), and agility measures were recorded. Eighteen subjects (mean ± SD; age 22.4 ± 2.0 years; BMI [body mass index] 26.9 ± 4.2 kg·m-2) foam rolled before testing each day, whereas 19 (mean ± SD; age 23.2 ± 3.2 years; BMI 26.3 ± 4.0 kg·m-2) served as a non-FR control (CON). Measurements recorded during the 5 days of recovery from the repeated sprint protocol were compared with week 1 baseline measurements. The area under the curve (AUC) was calculated by summing all 5 scores as they changed from baseline measurement, and these data were compared by condition using a 2-tailed Mann-Whitney U-test (alpha level = 0.05). Perceived soreness, hip abduction ROM, hamstring muscle length, and VJ were not significantly different between groups (p = 0.25). Agility was less impaired in the FR condition (p = 0.0049) as AUC was higher in CON (2.88 ± 2.45 seconds) than in FR (0.33 ± 2.16 seconds). Based on these data, FR appears to expedite recovery of agility after EIMD instigated by a repeated sprint protocol. Foam rolling may be useful for athletes requiring adequate agility who need to recover quickly from demanding bouts of exercise.